Effects of long-term functional training combined with blood flow restriction training on athletic performance and body composition in basketball athletes - Wang, D.; Lyu, M.; Li, Z.; Li, M.; Tao, Y.; Zhu, A. (Frontiers in Physiology, 2026)
Background: This study examined the effects of a 24-week functional training (FT) and blood flow restriction combined with FT (BFR-FT) on athletic performance and body composition in athletes.